Access to medicines: relations with the institutionalization of pharmaceutical services - Rafael Damasceno de Barros; Ediná Alves Costa; Djanilson Barbosa dos Santos; Gisélia Santana Souza; Juliana Álvares; Augusto Afonso Guerra Junior; Francisco de Assis Acurcio; Ione Aquemi Guibu; Karen Sarmento Costa; Margô Gomes de Oliveira Karnikowski; Orlando Mario Soeiro; Silvana Nair Leite (Universidade de São Paulo, 2017)
ABSTRACT OBJETIVE To analyze the relationship between access to medicines by the population and the institutionalization of pharmaceutical services in Brazilian primary health care. METHODS This study is part of the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos - Serviços 2015 (PNAUM - National Survey on Access, Use and Promotion of Rational Use of Medicines - Services 2015), a cross-sectional, exploratory, and evaluative study composed of an information survey in a representative sample of cities, stratified by Brazilian regions. Access was defined based on the acquisition of medicines reported by the patient, ranging between: total, partial, or null. The institutionalization of pharmaceutical services was analyzed based on information provided by pharmaceutical services providers and by those responsible for medicines delivery. Chi-square test and multinomial logistic regression were used in the statistical analysis. RESULTS Full access to medicines was greater when professionals affirmed there were the following aspects of the dimensions: "management tools," "participation and social control," "financing," and "personnel structure," with significant associations in the bivariate analysis. The "pharmaceutical care" dimension did not achieve such an association. After multinomial logistic regression, full access was more prevalent when those in charge of pharmaceutical services stated that: they always or repeatedly attend meetings of the Municipal Health Council, OR = 3.3 (95%CI 1.5-7.3); there are protocols for medicines delivery, OR = 2.7 (95%CI 1.2-6.1); there is computerized system for managing pharmaceutical services, OR = 3.9 (95%CI 1.9-8.0); those responsible for medicines delivery reported having participated in a course or training for professionals in the past two years, OR = 2.0 (95%CI 1.1-3.5); there is computerized system for pharmaceutical services management, OR = 4.3 (95%CI 2.4-7.5). CONCLUSIONS Aspects related to the institutionalization of pharmaceutical services have been strongly related to access to medicines. Our results indicate the need to prioritize its implementation, contributing to its consolidation in Brazil and to the effectiveness of health services regarding the purposes of pharmaceutical services policies.